Self-compassion Among First Year Boarding School Students - Maya Yasmin; Yuninda Tria Ningsih (Jurnal Neo Konseling, 2021)
This study aims to describe the self compassion amog first year boarding school students. This study used a quantitative approach with descriptive research methods involved 130 students in Bukittinggi, West Sumatera by using the random sampling technique. A questionnaire was used to collect data were self-compassion scale (SCS) adapted from Neff (2003) consisting of 26 question items to measure 3 dimensions of self compassion. The results of this study show that self compassion among first year boarding school students in the moderate category (64.6%) so it can be concluded that students are quite capable of showing openness and self-acceptance in facing various problems in their first year of education at the dormitory environment.